"Pure Land": Inhabiting the Mogao Caves at Dunhuang. (5th April 2013) - Kenderdine, Sarah
Abstract This article examines two exhibition installations that integrate high‐resolution digital archeological datasets (photography and 3D architectural models) with immersive, interactive display systems. These analogous installations, Pure Land: Inside the Mogao Grottoes at Dunhuang and Pure Land: Augmented Reality Edition, allow visitors to engage in different ways with a full‐scale augmented digital facsimile of Cave 220 from the UNESCO World Heritage site, the Mogao Grottoes, Gansu Province, northwestern China. The peerless treasuries of paintings and sculptures at Dunhuang are extremely vulnerable. Comprehensive digitization has become a primary method of preservation at the site. The digital facsimiles of this cultural paragon can be transformed, providing formative personal experiences for museum visitors. The Pure Land projects contribute to new strategies for rendering cultural content and heritage landscapes. Interpreting these installations through the lens of phenomenology and panoramic immersion helps situate them at the forefront of virtual heritage today.